Assessment of General and Local Anaesthesia on Respiratory Health Outcomes in Children Undergoing Full Mouth Rehabilitation for Early Childhood Caries: A Randomized Controlled Trial - K, Aarthi.; R, Ramesh; R, Mahesh (Journal of Neonatal Surgery, 2025)
Background: Early childhood caries (ECC) is a prevalent dental issue that often requires full mouth rehabilitation (FMR) under general anaesthesia (GA) for paediatric patients with limited cooperation. Although GA facilitates comprehensive treatment, it may increase the risk of respiratory complications, necessitating further investigation. Aim: To assess the impact of general anaesthesia (GA) and local anaesthesia (LA) on respiratory and oral health outcomes in children undergoing FMR for ECC. Materials and Methods: This randomized controlled trial was conducted in 144 children aged 3 to 6 years requiring FMR at Saveetha Dental College, Chennai, India. Participants were randomly assigned to GA or LA groups. Key outcomes included oxygen saturation (SpO₂), respiratory rate, postoperative respiratory complications, and oral health indicators such as the Plaque Index (PI), Gingival Index (GI), and DMFT index. Assessments were conducted preoperatively, postoperatively, and at follow-up visits. Statistical tests including t-tests, ANOVA, and regression analysis were performed. Results: Children in the GA group showed significantly improved SpO₂ levels, reduced PI and GI scores, and shorter recovery times. However, the GA group had a higher incidence of respiratory complications, such as coughing and wheezing. Regression analysis identified DMFT and GI scores as significant predictors of SpO₂ levels. Conclusion: While GA was associated with better oral health outcomes and improved oxygen saturation, it also increased the risk of respiratory complications. Emphasizing comprehensive preoperative assessment and careful postoperative monitoring is essential for enhancing safety in paediatric dental procedures under GA. Regression analysis identified postoperative respiratory complications as significant predictors of SpO₂ levels